Penggunaan Media Dadu Pertanyaan pada Mata Pelajaran Bahasa Indonesia Materi Penggunaan Kata Tanya untuk Meningkatkan Hasil Belajar Siswa Kelas II SDN 61/X Talang Babat - Nurhayati Nurhayati (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2020)
This study aims to improve student learning outcomes by using the media of question dice in Indonesian subjects on the use of question words for Class II SDN 61 / X Talang Babat. This research is a classroom action action (PTK). This research consisted of 2 cycles. The stages of each cycle are the stages of planning, observing, observing and reflecting on actions. The research subjects were students of class II SD Negeri 61 / X Talang Babat in the second semester of the 2018/2019 academic year, which amounted to 28. The data of this study were text and numbers regarding the understanding of major learning outcomes using question words. Observation data through and tests. The result of the research states that the improvement of learning using question dice media can improve student learning outcomes. It can be seen from the results of observations and evaluations that have been carried out in cycles I and II in the implementation of this Classroom Action Research. The average learning outcomes obtained by students in the first cycle was 71.46 and in the second cycle the students' average was 77.5. Meanwhile, the percentage of students who did not complete the learning process decreased from the first cycle to 40% and the second cycle to 14%. From the results of this study shows that there is an increase in Learning Outcomes with the Use of Question Dice Media in grade II SDN 61 / X Talang Babat in the 2018/2019 Academic Year.